2017
DOI: 10.1098/rspb.2017.0953
|View full text |Cite
|
Sign up to set email alerts
|

Skill not athleticism predicts individual variation in match performance of soccer players

Abstract: Just as evolutionary biologists endeavour to link phenotypes to fitness, sport scientists try to identify traits that determine athlete success. Both disciplines would benefit from collaboration, and to illustrate this, we used an analytical approach common to evolutionary biology to isolate the phenotypes that promote success in soccer, a complex activity of humans played in nearly every modern society. Using path analysis, we quantified the relationships among morphology, balance, skill, athleticism and perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 42 publications
6
55
0
2
Order By: Relevance
“…Our study complements related findings in Tour de France cyclists (Postma 2014) and mixed martial artists (Little et al 2015) and adds to the nascent field of evolutionary sports science (Wilson et al 2017), highlighting the value of sports data as a rich resource for investigating how selection acts on psychological and physiological aspects of athletic performance. Using annual performance measures from the biathlon World Cup, we found that male, but not female, biathletes who had achieved a higher career peak were rated as more physically attractive by the opposite sex.…”
Section: Discussionsupporting
confidence: 70%
“…Our study complements related findings in Tour de France cyclists (Postma 2014) and mixed martial artists (Little et al 2015) and adds to the nascent field of evolutionary sports science (Wilson et al 2017), highlighting the value of sports data as a rich resource for investigating how selection acts on psychological and physiological aspects of athletic performance. Using annual performance measures from the biathlon World Cup, we found that male, but not female, biathletes who had achieved a higher career peak were rated as more physically attractive by the opposite sex.…”
Section: Discussionsupporting
confidence: 70%
“…What has been observed, however, is that a combined RG1 across the whole cohort was statistically older than all the other ranking groups, by ~2 years. This demonstrates that the physiological effects of age are not necessarily the key variables to consider when assessing a competitor's potential performance, a finding which has recently been reflected in both team and combat sports (Wilson et al, 2017). As RG2 -RG5 across the whole cohort had very similar age profiles, this suggests that the increased skill mastery and experience that comes with age can outweigh the physiological decrements, at least in the short term, so older competitors are able to maintain a relatively high ranking once this level has been reached.…”
Section: Discussionmentioning
confidence: 93%
“…Our results have broader implications for the debate over trade-offs between speed and endurance in animal locomotion. As such, our work demonstrates the potential for insights that can be drawn from exploring the connections between human performance, sports science and evolutionary biology, a point recently made by Wilson et al [17]. Trade-offs are a common and appealing idea in biology and beyond (e.g.…”
Section: Discussionmentioning
confidence: 51%